Fine-tuning optimal porous coordination polymers using functional alkyl groups for CH4 purification. Issue 34 (19th July 2017) - Cheng, Fujun; Li, Qianqian; Duan, Jingui; Hosono, Nobuhiko; Noro, Shin-ichiro; Krishna, Rajamani; Lyu, Hongliang; Kusaka, Shinpei; Jin, Wanqin; Kitagawa, Susumu
Abstract : By optimizing the position and length of the shortest two alkyl groups in the channels, we developed a porous material with integrated structural properties for feasible adsorption- and membrane-based CH4 purification at room temperature. Abstract : Nano-porous coordination polymers (nano-PCPs), as a new class of crystalline material, have become a lucrative topic in coordination chemistry due to the facile tunability of their functional pore environments. However, elucidating the pathways for the rational design and preparation of nano-PCPs with various integrated properties for feasible gas separation remains a great challenge. Here, we demonstrate a new route to achieve nano-PCPs with an integrated pore system and physical properties using a reticular chemistry strategy. By optimizing the position and length of the shortest two alkyl groups in the channels, unprecedented phenomena of improved surface area, gas uptake, gas selectivity, thermal stability and chemical stability were observed in the PCPs, especially inNTU-14, the structure with a pendant ethyl group. Furthermore, the high performance of adsorption- and membrane-based separation makesNTU-14 a promising medium for CH4 purification from a mixture at room temperature.